Reformasi Kebijakan Pengawas Dana BOS: Studi Tentang Upaya Peningkatan Transparansi dan Akuntabilitas di Madrasah - Harmendra (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This Policy Paper aims to analyze the causes and impacts of the lack of interest in the Treasury Officer position at the Ministry of Religious Affairs (Kemenag) Office in Rokan Hilir Regency, which has resulted in the practice of one individual holding the position of Expenditure Treasurer for several Work Units (Satker). This problem indicates a serious gap in human resource (HR) management and state financial governance at the regional level, which has the potential to create the risk of budget mismanagement and violations of the principles of transparency and accountability. The writing method used is a qualitative case study approach, collecting data through in-depth interviews with relevant parties, as well as a documentary study of financial reports and internal regulations of the Ministry of Religious Affairs of Rokan Hilir. Data analysis was conducted using an interactive model, which includes data reduction, data presentation, and drawing conclusions. Preliminary results indicate that several factors contribute to this phenomenon, such as heavy workloads, lack of adequate financial incentives, career limitations, and a lack of appreciation for the strategic role of treasurers. The implications of this dual position include decreased effectiveness of financial oversight, potential errors in reporting, and an increased risk of abuse of authority. This study is expected to provide concrete policy recommendations to relevant parties, including reforming the incentive system, improving human resource capacity, and re-evaluating the organizational structure to ensure every key position is filled by competent and dedicated individuals.